In vitro antibacterial evaluation of Anabaena sp. against several clinically significant microflora and HPTLC analysis of its active crude extracts - Chauhan, Abhishek (Medknow Publications, 2010)
The present study was conducted to evaluate the possible antibacterial activity of Anabaena extracts. Anabaena was isolated from a natural source and cultured in vitro. after suitable growth, cyanobacterial culture was harvested using different solvents. Extracts, thus prepared, were evaluated for their antibacterial potential by agar-well diffusion assay against bacterial species of clinical significance. MIC values were determined further to check the concentration ranges for significant inhibition. HPTLC analysis was done to separate the components of active crude extract in an attempt to identify the bio-active chemical entity. Methanol extract exhibited more potent activity than that of hexane and ethyl acetate extracts. No inhibitory effect was found against Pseudomonas aeruginosa, Salmonella typhi, and Klebsiella pneumoniae. Staphylococcus aureus required about 256 µg/ml of the crude methanol extract for effective inhibition. HPTLC evaluation at λ 254 nm was performed for the separation of a complex mixture of the methanol extract. The results provide evidence that Anabaena sp. extracts might indeed be potential sources of new antibacterial agents.